Nutritional Value Content in Mangrove Syrup From Sonneratia alba Fruit - Wintah Wintah; Kiswanto Kiswanto; Endah Sulistiyowati; Fitrah Reynaldi (Universitas Teuku Umar, 2021)
Pedada fruit (Sonneratia alba) is a fruit of mangrove plants whose utilization can be improved through simple technology, namely the processing of Sonneratia alba fruit into syrup. Mangrove plants produce fruit that can be utilized as a processed beverage, one of which is Sonneratia alba fruit that has a sour taste and can be processed into fresh drinks in the form of mangrove syrup. The purpose of the study was to find out the nutritional value content of mangrove syrup from Sonneratia alba fruit. Research methods are experiments. We use proximal analysis, which includes tests on protein, fat, carbohydrate, and vitamin C. Proximal analysis is carried out at the organic chemistry laboratory, Faculty of MIPA Universitas Jenderal Soedirman. The results of our research show Processed mangrove syrup from Sonneratia alba fruit has nutritional content: protein 1.20%, fat 0.20%, carbohydrates 3.50%, and vitamin C 55.30%. Mangrove fruit from Sonneratia alba processed into syrup has a high nutritional and antioxidant value and is rich in fiber, which is good for health